Quality Evaluation of Ethambutol Hydrochloride Tablet Batches Available in Governmental Health Facilities of Jimma Town, Southwest Ethiopia - Meseret Yirdaw; Belachew Umeta; Yimer Mokennen (Hindawi Limited, 2021)
Background. The availability of poor-quality drugs on the drug market might favor the ineffectiveness of the drug and/antimicrobial resistance. Aim. To evaluate the quality of similar batches of ethambutol hydrochloride tablets available in different governmental health facilities of Jimma town, southwest Ethiopia. Methods. The World Health Organization checklist was used to inspect the storage area of health facilities and check medicines for the sign of counterfeit. The test was conducted as per the United States Pharmacopeia on six similar batches of ethambutol hydrochloride sampled from different governmental health facilities. Data were analyzed using SPSS version 20, and one-way ANOVA was used for comparing the dissolution profile and weight variation of batches. Results. Three health facilities did not comply with the storage area specifications for pharmaceuticals. No batches have shown any sign of counterfeit. All of the tablet batches tested complied with USP specifications for weight variation, percentage purity, and dissolution test. Conclusions and Recommendation. The entire tablet batches complied with the World Health Organization specification for packaging and labelling of pharmaceuticals. All tablet batches complied with the test for weight variation, purity of drug substance, and dissolution. Since some health facilities did not comply with at least one specification for storage of pharmaceuticals, regulatory agencies and stack holders are advised to inspect the health facilities to ensure appropriate storage of pharmaceuticals in health facilities.